NINA'S OBSESSION TO BE PROFESSIONAL DANCER IN DARREN ARONOFSKY'S BLACK SWAN (2010) MOVIE: A HUMANISTIC PSYCHOLOGICAL APPROACH - SISWANTO, SISWANTO (2011)
This study is aimed to show the Nina‟s obsession to be professional dancer gender inequality in Darren Aronofsky‟s Black Swan (2010) by using a humanistic psychological approach. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing the Nina‟s obsession based on the a humanistic psychological approach. This research is qualitative research. Type of data of the study is text taken from two data sources: primary and secondary. The primary data source is Black Swan (2010) movie by Darren Aronofsky. While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The outcome of the study shows the following conclusions. Firstly, based on the structural analysis indicated that each of narrative elements of movie have been related into solid unity. Secondly, based on humanistic psychological approach, the researcher divided the need into five elements which is consisting of physiological needs, safety and security needs, belongingness and love needs, self-esteem needs, and self-actualization needs. Self actualization needs also found in forms of two kinds; the need for privacy and efficient perception of reality. As a ballerina, she has a beautiful dream in her life; she wants to be the major player on the "Swan Lake‟ Ballet performance. This is her needs that she really wants to be a good ballerina dancer. Nina also has a basic need, such as need for love and sex. The love and sex become the main problem of Nina in a physiological needs, safety and security needs, belongingness and love needs, self-esteem needs, and self-actualization needs..